Real‐world stroke prevention strategies in nonvalvular atrial fibrillation in patients with renal impairment. (16th May 2017) - Mert, Kadir U.; Mert, Gurbet Ö.; Başaran, Özcan; Beton, Osman; Dogan, Volkan; Tekinalp, Mehmet; Aykan, Ahmet Ç.; Kalaycıoğlu, Ezgi; Bolat, Ismail; Taşar, Onur; Şafak, Özgen; Kalçık, Macit; et al.
Abstract: Background: The data regarding stroke prevention strategies in nonvalvular atrial fibrillation (NVAF) are limited especially in patients with renal impairment (RI). We sought to evaluate management dilemmas in patients with concurrent NVAF and RI in RAMSES (ReAl‐life Multicenter Survey Evaluating Stroke Prevention Strategies inTurkey) study. Methods: We conducted a prospective, multicenter, nation‐wide registry in NVAF patients in outpatient cardiology clinics. All consecutive patients with NVAF were enrolled in RAMSES study (ClinicalTrials.gov identifier NCT02344901). The baseline data were collected. Glomerular filtration rate (GFR) was estimated by Cockcroft–Gault equation. Results: A total number of 6273 patients from 29 provinces of Turkey with the contribution of 83 investigators were enrolled to the study. Of the study population, 1964(33%) patients had RI which was defined as GFR < 60 mL/min. Patients with RI had significantly higher CHA2 DS2 VASc and HAS‐BLED scores compared to those without RI (3·9 ± 1·5 vs. 2·9 ± 1·5, and 2·0 ± 1 vs. 1·4 ± 1; P < 0·001). Prior history of major bleeding (6·9% vs. 4·1%, P < 0·001) and stroke (16·2% vs. 11·8%, P < 0·001) was significantly higher among individuals with concomitant RI and NVAF. Although RI patients had a higher risk for thromboembolism, number of the patients who did not receive any anticoagulant therapy was higher in patients with RI than without RI (30·1 vs. 26·4%, P = 0·003). Conclusion: RAMSES study showed that one‐third of the patients with NVAF had RI in the real‐world setting. Although it is mandatory in most of the patients with concomitant NVAF and RI, nearly one‐third of these patients did not receive any anticoagulant therapy.